Radical martyrdom and cosmic conflict in early Christianity - Middleton, Paul (Library of New Testament studies, 2006)
In the early Church, several views on martyrdom co-existed. The 'orthodox' position, generally accepted by scholars, was that a Christian should choose martyrdom rather than deny the Faith, but should not, on any account, court death. Although it has been recognized that some in the early Church did in fact seek out death, by giving themselves over to arrest, most scholars have dismissed these martyrs as 'deviant,' 'heretical,' and not displaying 'the normal Christian attitude to martyrdom.' Therefore, instances of volitional, or radical martyrdom, have been largely ignored in scholarly investigation into the theology and origins of Christian martyrdom. However, this project argues that, far from being a deviant strand of early Christianity, radical martyrdom was a significant, and widely held idealized form of Christ-devotion in the late first to early third centuries. Since scholars have largely carried out historical and theological investigations without reference to radical martyrdom, their conclusions are incomplete. This project aims to make up for this omission, re-examining the presentation, theology, and origins of Christian martyrdom up to the beginning of the Decian persecutions. Christian martyrdom is placed within the heritage of Jewish War tradition, with each martyr making an important contribution to the cosmic conflict between Satan and God.